PEMETAAN EKOSISTEM PADANG LAMUN BERESOLUSI TINGGI DENGAN METODE CLOSE RANGE PHOTOGRAMMETRY - Nasution, Muhammad Arif (Universitas Teuku Umar, 2019)
Several remote sensing methods using satellite imagery and acoustic instruments have often been used in mapping aquatic ecosystems but expensive and need hight expertise. This method used in this study is quite new in mapping aquatic ecosystems, but has often been done in mapping terrestrial areas. This method produces clear high-resolution digital data using optical devices with high efficiency. This research was carried out in Pulau Matahari, Kepualauan Banyak, Aceh Singkil for 3 (three) months in the field and 2 (two) months of data processing. This research data is in situ primary data taken by taking optical images continuously from the surface of the water by swimmer using a waterproof digital camera and then processed with PhotoScan software. The results of this study are high-resolution digital image data that can be used to make seagrass ecosystems map at the study site, assess ecosystem status, identify seagrass species ( 4 species), density (St1:103,9 ind/m2 and St2:128 ind/m2) and seagrass cover (57%– 61%).